Effects of Probiotic Consumption on Absence Seizures - ONAT, FİLİZ; KARAMAHMUTOĞLU, TUĞBA (KARE PUBL, 2017)
Objectives: Probiotics are microorganisms of intestinal microflora that are beneficial for human health. Childhood absence epilepsy has 2 validated rat models: Genetic Absence Epilepsy Rats from Strasbourg (GAERS) and Wistar Albino Glaxo from Rijswijk (WAG/Rij). To date, there have been no clinical or experimental studies of the effects of probiotics on absence epilepsy. The present study was an investigation of the effects of probiotics on absence seizures in the GAERS rat model. Methods: GAERS were used to examine the effects of probiotics. Nine male GAERS were assigned to 1 of 2 groups (probiotic or control). The animals had free access to food and water. Commercially available probiotic product was provided in drinking water to probiotic group for 1 month. Surface electrodes were then implanted for electroencephalogram (EEG) recordings. Two aspects of EEG recordings were compared: cumulative duration and cumulative number of absence seizures. Results: Analysis of spike-and-wave discharges between the 2 groups showed no significant difference in either cumulative duration or number (p>0.05). Additionally, it was observed that probiotic group consumed more water than control group (p<0.05). Conclusion: Results indicated that probiotic consumption had no effect on duration or number of spike-and-wave discharges of GAERS after 1-month feeding period. This is the first investigation in the literature addressing interactions between probiotics and absence epilepsy, and further research is needed.
Keywords: Childhood absence epilepsy; Genetic Absence Epilepsy Rats from Strasbourg; probiotics; rat; EPILEPSY; RATS; MECHANISMS; BEHAVIOR; MOUSE; MODEL; GAERS; ACID; MICE